Dynamic Response of Crossanisotropic Layered Media with Imperfect Interface under Axisymmetric Loads. (10th December 2022) - Han, Zejun; Guo, Chengchao; Yang, Linqing; Zhang, Jin; Sun, Kai
Abstract : Considering the incomplete contact between the adjacent layers of crossanisotropic multilayered half-space media, an algorithm was derived based on the spectral element method (SEM) to determine the dynamic response at any point of the medium when an axisymmetric harmonic load is applied. The algorithm used two equivalent contact parameters to simulate the relationship between the discontinuity of the displacement and stress. The SEM was employed for the summation in the integral calculation to avoid the infinite integral in the integral transformation and greatly improve the efficiency of the solution to the dynamic response of the crossanisotropic layered half-space medium. The accuracy of the developed method is verified by the numerical examples as well as the efficiency of the developed method. Finally, an extensive parametric analysis of the contact parameters of the interface between the layers of the layered medium, namely, the point of the application of the external load, the excitation frequency, and the heterogeneous properties of the layered medium was conducted, providing a reliable numerical basis for engineering practice.